2001
DOI: 10.1093/humrep/16.12.2583
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian response during IVF–embryo transfer cycles after laparoscopic ovarian cystectomy for endometriotic cysts of >3 cm in diameter

Abstract: The number of oocytes and embryos obtained was not significantly decreased by laparoscopic cystectomy, suggesting that in experienced hands this procedure may be a valuable surgical tool for the treatment of large ovarian endometriomas. However, great care must be taken to avoid ovarian damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
14

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(81 citation statements)
references
References 22 publications
2
65
0
14
Order By: Relevance
“…This area is revealed by lyses of adhesions between the ovary and the adjacent broad ligament, leading to characteristic 'chocolate fluid' evacuating from the cyst. The excision by scissors of area A allows the surgeon to identify a cleavage plane close to the cyst wall, which may be followed without significant bleeding (area B; Canis et al, 2001). Where adhesions are revealed in the cleavage plane, they should be coagulated and cut, so as not to strip the ovarian cortex.…”
Section: Methodsmentioning
confidence: 99%
“…This area is revealed by lyses of adhesions between the ovary and the adjacent broad ligament, leading to characteristic 'chocolate fluid' evacuating from the cyst. The excision by scissors of area A allows the surgeon to identify a cleavage plane close to the cyst wall, which may be followed without significant bleeding (area B; Canis et al, 2001). Where adhesions are revealed in the cleavage plane, they should be coagulated and cut, so as not to strip the ovarian cortex.…”
Section: Methodsmentioning
confidence: 99%
“…17 Canis et al and Marconi et al found no effect on ovarian response in IVF after cystectomy. 18,19 But, there are many other trials that indicate that cystectomy has a bad influence in the subsequent ovarian responsiveness. As Hart et al concluded, excisional surgery of endometriomas results in a more favorable outcome than drainage and ablation in terms of recurrence, pain symptoms, subsequent spontaneous pregnancy in previously sub-fertile women, and ovarian response to stimulation.…”
Section: Fenestration and Ablation (Fulguration Or Vaporization)mentioning
confidence: 99%
“…Furthermore, they pointed that removing endometrioma did not affect the quality of oocyte in IVF cycle as an evidence of no additional advantage of surgery in ART cycle [27]. On the other hand, some investigators did not support the same opinion [28][29][30][31]. It is clear that considerable surgical expertise is requied to decrease ovarian damage and avoid incomplete surgery [32].…”
Section: Management Of Infertilitymentioning
confidence: 99%